Pengaruh Review Produk Tiktok Terhadap Keputusan Membeli Pada Generasi Z di Indonesia - Susan Amelia; Selfi Putri Lestianingrum; Fikri Rizki Utama (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
The rapid advancement of digital technology and the increasing use of social media have significantly transformed how consumers search for information and make purchasing decisions, particularly among Generation Z. TikTok has emerged as a highly influential platform due to its short, creative, and authentic product review content that can shape consumer perceptions and drive purchase intentions. This study aims to analyze the influence of TikTok reviews, trust in reviewers, and the visual appeal of content on the purchasing decisions of Generation Z in Indonesia. Using an associative quantitative approach, data were collected through an online questionnaire distributed to 100–150 eligible respondents. The data were analyzed using multiple linear regression with IBM SPSS Statistics 25. The results indicate that all three independent variables have a positive and significant impact on purchase decisions. These findings highlight the strategic role of user-generated content in shaping young consumers’ behavior in the digital era. This study is expected to contribute to the digital marketing literature and provide practical insights for businesses in optimizing their promotional strategies through social media.